Trans intracommunity support & knowledge sharing in the United States & Canada: A scoping literature review. (13th January 2021) - Harner, Vern
Abstract: Intracommunity support and knowledge sharing is used in transgender ("trans") communities as they navigate systems of oppression. Even for individuals with access to accepting families and service providers, connecting with other trans individuals can provide useful insight and resources. Conducted between December 2018 and April 2019, this scoping literature review examines the extent, range and nature of research activity regarding intracommunity knowledge and support sharing within trans communities. Drawing from Weeks' framework regarding sexual communities and the concepts of positive in‐group identity and group‐level coping, this review specifically addresses the guiding questions of what, how and why knowledge and support are shared within trans communities. Empirical studies conducted between 2004 and 2019 in the United States and Canada that were published in English and had a discernible trans sample or subsample were included. Thirty‐one studies met the criteria. Key themes from this literature are (a) sharing information related to advocacy & education, identity/expression and personal stories/experience while (b) utilising an array of both online and/or in‐person methods in order to (c) build community/support and navigate identity development and transition. Implications from the review, including impacts on both clients and students in social work and care programs, are discussed.